Punsishment for The Crime of Fraud Using A Fake Identity Is Reviwed From Islamic Law - Fernando, Youngky (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2022)
The purpose of this research is to determine the review of Islamic criminal law regarding perpetrators of criminal acts of fraud using fake identities. The data collection technique uses the library research method and uses descriptive data, in-depth direct interviews with respondents. This research is a descriptive analysis which aims to explain data about fraud using fake identities which is then analyzed using theories in Islamic law. The results of the research show that there is a specific and detailed explanation regarding the meaning of fraud using a fake identity regarding fraud using a fake identity, but in Islamic law there is no punishment for this criminal act. So we see similarities with the Baitul Maal stamp fraud case during the time of Umar bin Khattab, which punished the perpetrator with ta'zir, namely, being whipped 100 times and exiled for a year. From the explanation above, it can be concluded that the punishment for perpetrators of fraud using fake identities is ta'zir.